2016
DOI: 10.1104/pp.16.00613
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates from Host Plants Influence Growth of the Parasitic Plant Cuscuta gronovii and Its Susceptibility to Aphid Feeding

Abstract: Parasitic plants acquire diverse secondary metabolites from their hosts, including defense compounds that target insect herbivores. However, the ecological implications of this phenomenon, including the potential enhancement of parasite defenses, remain largely unexplored. We studied the translocation of glucosinolates from the brassicaceous host plant Arabidopsis (Arabidopsis thaliana) into parasitic dodder vines (Convolvulaceae; Cuscuta gronovii) and its effects on the parasite itself and on dodder-aphid int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 100 publications
2
24
0
Order By: Relevance
“…Glucosinolates include some of the very first secondary metabolites (i.e., compounds that do not function in plant growth and reproduction) known to deter generalist herbivores and to stimulate specialist herbivores (Vershaffelt, 1910; Fraenkel, 1959), and they continue to feature prominently in modern plant biology and entomology (e.g., Wheat et al, 2007; Clay et al, 2009). The development of Arabidopsis mutants that are altered in glucosinolate production has presented exciting opportunities to test the importance of these compounds in planta for purposes of science (e.g., Müller et al, 2010; Rohr et al, 2012; Schramm et al, 2012; Smith et al, 2016) and, we suggest, for the purpose of education.…”
Section: Resultsmentioning
confidence: 99%
“…Glucosinolates include some of the very first secondary metabolites (i.e., compounds that do not function in plant growth and reproduction) known to deter generalist herbivores and to stimulate specialist herbivores (Vershaffelt, 1910; Fraenkel, 1959), and they continue to feature prominently in modern plant biology and entomology (e.g., Wheat et al, 2007; Clay et al, 2009). The development of Arabidopsis mutants that are altered in glucosinolate production has presented exciting opportunities to test the importance of these compounds in planta for purposes of science (e.g., Müller et al, 2010; Rohr et al, 2012; Schramm et al, 2012; Smith et al, 2016) and, we suggest, for the purpose of education.…”
Section: Resultsmentioning
confidence: 99%
“…This relationship could be due to allelochemicals (terpenes, long-chain fatty acids, phenols, phenolic acids and lactone) that are present in the parasitic weed species C. campestris (Khanh et al, 2008, Smith et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that the genetic suppression of MYC function in the myc234 mutant increases aphid attraction by releasing different volatiles and potentially also by modifying composition of plant metabolites [54]. In the quad mutant, the synthesis of both indole and aliphatic glucosinolates is impaired, but no impact on M. persicae population growth was reported [49,55]. Although M. persicae should not be in contact with vacuolar glucosinolates-hydrolyzing myrosinases when ingesting sap, indole glucosinolates are nonetheless degraded in the aphids and this degradation may be responsible for the deterrent effect of these compounds on aphids [14].…”
Section: Effect Of the Mutations And Tuyv Infection On Aphid Feeding mentioning
confidence: 99%